Pelet Dibuat Dari Maggot (Hermetia illucens ) BSF Dengan Media Kotoran Sapi dan Bungkil Sawit Sebagai Pakan Ikan Lele Dumbo (Clarias gariepinus B) - Syahrizal, Syahrizal; Safratilofa, Safratilofa (Jurnal Akuakultur Sungai dan Danau, 2025)
Feed factor is the main variable besides water quality and other environment that determines the growth, survival and health of fish. The feed design of this study aims to analyze the provision of catfish pellets from maggots (Hermetia illucens) and fermented media of cow dung (PKS) and palm kernel meal (PBS) during one cycle of BSF (Black Soldier Fly) 21 days. The design used was a Completely Randomized Design with 4 treatments and 3 replications, with treatment A (PBS 100.00%: PKS 00.00); B (PBS 75.00%: PKS 25.00%), C (PBS 50.00%: PKS 50.00%), and D (PBS 00.00%: PKS 100.00%). The results of this study are in the form of parameter variables for the the best average proximate organic media raw materials at the beginning and ending of B (protein 21.74% and 23.74%), the best feed proximate was also at B (protein 37.51% with energy 415.57 grams/Kcal.), the highest average organic media production in treatment B (1319.34 grams), followed by A (1148.68 grams) and the lowest in D (362.34 grams), the best maggot biomass in A (157.34 grams) followed by B (106.34 grams) and the lowest D (89.01 grams). The highest wet pellet production was obtained in treatment A (564.33 grams) followed by B (486.67 grams) and the lowest D (362.33 grams). The average weight of the best individual maggot in treatment A (0.26 grams/tail), followed by B (0.22 grams), the lowest D (0.18 grams/tail) and the best individual maggot length in treatment A (1.55 cm), followed by B (1.15 cm) and the lowest C (0.93 cm). The number of maggot individuals at the end of the best A (25.45 Ind/gram) followed by B (22.00 Ind/gram) and the lowest D (17.57 ind/gram). The best organic maggot biomass media product was in treatment A (157.34 Ind/2.5 kg substrate) followed by B (176.34 Ind/2.5 kg substrate) and the lowest in D (89.01 Ind/2.5 kg substrate). The highest ESE (organic substrate efficiency) of maggot material was in treatment A (6.30%) and the lowest in D (3.57), the best ESE residual bioconversion value was D (56.61%) and the lowest in A (45.40%). The results of the pellet feeding test on dumbo catfish (Clarias gariepinus B) showed that the best treatment was in treatment B with an average weight of 9.89 gram/Ind, length 4.07 cm/Ind, survival rate 100%, and FCR 1.52. Water quality that supports temperature 26-29, pH 7.6-7.8, DO 5.2-7.2 ppm, and ammonia 0.011-0.014 mg/L.